2008
DOI: 10.1038/mt.2008.132
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Hexon Hypervariable Region 5 of Adenovirus Serotype 5 Abrogates Blood Factor Binding and Limits Gene Transfer to Liver

Abstract: Liver tropism potentially leading to massive hepatocyte transduction and hepatotoxicity still represents a major drawback to adenovirus (Ad)-based gene therapy. We previously demonstrated that substitution of the hexon hypervariable region 5 (HVR5), the most abundant capsid protein, constituted a valuable platform for efficient Ad retargeting. The use of different mouse strains revealed that HVR5 substitution also led to dramatically less adenovirus liver transduction and associated toxicity, whereas HVR5-modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 36 publications
5
91
0
Order By: Relevance
“…After PBS-5% milk-0.05% IgePal (Sigma) blockage of free sites, the membrane, was incubated with 10 11 vp of different Ad in PBS-0.5% milk-0.05% IgePal, for 4 h at room temperature and processed as described previously. 36 …”
Section: Detection Of Adenoviral Genomementioning
confidence: 99%
See 1 more Smart Citation
“…After PBS-5% milk-0.05% IgePal (Sigma) blockage of free sites, the membrane, was incubated with 10 11 vp of different Ad in PBS-0.5% milk-0.05% IgePal, for 4 h at room temperature and processed as described previously. 36 …”
Section: Detection Of Adenoviral Genomementioning
confidence: 99%
“…High b-gal activity was documented in liver lysates of Adwt-and AdFNGR-injected mice, but not in AdHGNR-injected mice (Supplementary Figure 1a-b), as we previously observed for different hexon-modified Ads. 36 AdHNGR was shown to bind to immobilized blood factors FIX and FX, but was unable to use FX to Figure 1c-d). In tumor lysates, low b-gal activity was measured with no difference between groups (data not shown), thus suggesting that Ad liver uptake precludes efficient targeting.…”
Section: Cd13 and Avb3 Integrins Involvement In Ngr-dependent Cell Entrymentioning
confidence: 99%
“…Indeed, only factor X can rescue liver transduction in warfarin-anticoagulated mice. 22 Recently, it has been shown that the ␥-carboxyglutamic acid domain of factor X binds in a calcium-dependent manner to hexon protein in Ad5 8,22,23 and that this binding occurs at the cup formed by the center of each hexon trimer. Moreover, Ads with a high affinity for factor X, such as the species C serotypes Ad2 and Ad5, have been shown to efficiently transduce hepatocytes following i.v.…”
Section: In Vitro and In Vivo Transduction By Adenoviral Vectorsmentioning
confidence: 99%
“…[4][5][6] Several studies have documented the role of blood coagulation factors in mediating liver gene transfer in vivo and the mechanism underlying Ad5 hepatocyte transduction. [7][8][9][10][11][12] We demonstrated that coagulation factor X (FX) binds to the hexon protein of Ad5 at high affinity (B2 nM) and that this interaction mediates hepatocyte transduction following i.v. delivery in mice and rats.…”
mentioning
confidence: 99%